2019
DOI: 10.1111/sjop.12534
|View full text |Cite
|
Sign up to set email alerts
|

Don't cheat, be happy. Self‐control, self‐beliefs, and satisfaction with life in academic honesty: A cross‐sectional study in Poland

Abstract: Błachnio, A. (2019). Don't cheat, be happy. Self-control, self-beliefs, and satisfaction with life in academic honesty: A cross-sectional study in Poland. Scandinavian Journal of Psychology, 60, 261-266.Academic dishonesty is dishonest behavior at school or university which is supposed to result in a passed exam or in a positive grade. Academic dishonesty is a global problem, present at every stage of education. Since the consequences of this phenomenon may be serious, such as a low level of knowledge despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
2
16
0
4
Order By: Relevance
“…A similar study conducted on participants from 31 schools also demonstrated that the actual prevalence of cheating was 4.7%, while the perceived prevalence was 39%, similar to our study [24]. At the same time, some other studies indicate a substantial correlation between perception and prevalence [25,26].…”
Section: Discussionsupporting
confidence: 90%
“…A similar study conducted on participants from 31 schools also demonstrated that the actual prevalence of cheating was 4.7%, while the perceived prevalence was 39%, similar to our study [24]. At the same time, some other studies indicate a substantial correlation between perception and prevalence [25,26].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that cheaters generally have lower levels of self-esteem and self-efficacy than non-cheaters (Miller et al, 2007;Blachnio and Weremko, 2011;Błachnio, 2019). This result implies that people who are more afraid of failure and who lack self-esteem are more likely to use cheating to achieve their goals (Fontaine, 2006), and also suggests that low levels of self-esteem can adversely affect the behaviors that comply with rules and norms.…”
Section: Potential Factors Related To Cheating In Online Gamesmentioning
confidence: 97%
“… Ryska (2003) has shown that sports players with high level of self-esteem or mastery are more likely to have a high degree of sportsmanship. Low self-esteem is related to disruptive behavior in sports, such that cheaters are generally known to show lower levels of self-esteem than non-cheaters ( Miller et al, 2007 ; Błachnio, 2019 ). Thus, this study focuses on competitive motivation, self-esteem, and aggression as primary factors related to cheating in online games.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors [18] administered the Academic Honesty Scale, the Brief Self-Control Scale, the Social Success Index, the Normalcy Feeling Scale, the Social Comparison Scale, and the Satisfaction With Life Scale to a sample of 631 Polish respondents, and found self-regulation to be inversely related to academic cheating. The study also found a gender gap when engaging in academic cheating.…”
Section: Literature Reviewmentioning
confidence: 99%